The Cab Rank Rule: A Reappraisal of the Duty to Accept Clients - Quinlivan, Maree (Victoria University of Wellington Law Review, 1998)
Inevitably at some time in a lawyer’s professwnal life they will be requested to act for a client or cause which they find distasteful. They may have to answer the question of whether they would assist a remorseless killer to escape conviction on the ground of a mere legal technicality, or whether to refuse to prepare legal instruments that would or assist industrialists in pollution, or perhaps to provide legal advice regarding the avoidance of obligations under family law legislation. Such ethical dilemmas focus upon the legal representation of distasteful causes or clients. This article discusses the duty that a lawyer has as a ’legal professional’ to undertake such representations. It considers the ideological foundation upon which this duty is built, and the consequences of the duty. It compares the English system, where the freedom to chose which clients to represent is denied, with the American system, where such freedom is honoured. From this comparison the American system is preferred, and reform of the New Zealand system is advocated .